Books, children and censors. The continued disparagement of Children´s Literature - Sánchez-García, Sandra (Anuario ThinkEPI, 2023)
In the twenty-first century, that of social networks, multiplicity of communication channels, and freedom of expression, it may seem that censorship is something of the past, typical of conservative governments. However, the reality is that we are currently facing another type of censorship, that of "political correctness," especially in terms of readers who are children. More and more, this type of censorship silently coerces authors, publishers, teachers, and librarians in their relationship with books and readers. In this article we reflect on the role of literature as a socializing agent in addition to focusing on the reading competence of children and young people, understanding reading as a democratic and liberating process.